Participation of Socio-Economic Empowerment Groups in Improving the Economy in Rural Areas - Utami, Wahyu; Sulaiman, Adhi Iman; Windiasih, Rili; Sari, Lilik Kartika (Technium Sustainability, 2024)
Agricultural institutions play a crucial role in agricultural development as they can enhance the quality of human resources, increase production and income, and improve farmers’ welfare. Participation of socio-economic empowerment groups in improving the economy in rural areas in various aspects is essential to achieve these goals. This study aims to describe the characteristics of the research subjects and their participation from both internal and external aspects. The internal aspect is based on the benefits received, while the external aspect is influenced by local socio-cultural factors, agricultural extension workers’ guidance, and leaders’ capabilities. The research employs mixed methods, with data collection techniques including questionnaires, observations, in-depth interviews, and Focus Group Discussions (FGD). The data are analyzed using descriptive statistical analysis. The informants consist of members of the Leading Farmer and Fishermen Contact (LFFC) Padamara and field extension officers. The research was conducted in the agricultural institutions of Padamara District, Purbalingga Regency, and Central Java. The results show: (1) The majority of the research subjects are male (85%), aged 46 – 60 years (45%), with high school education (60%), earning 1,000,000 – 2,000,000 per month (65%), and have been members of LFFC for more than 3 years. (2) Participation from the internal aspect, based on the benefits received by members, shows a very high level of agreement. (3) Participation from the external aspect, including the culture of cooperation, also shows a very high level of agreement.